Self-efficacy in English language oral communication skills of technical trainees - Idrus, H. (2013)
The objective of the paper is to examine how the self-efficacy level of technical trainees affects their ability to speak in English. The paper also examines the self-efficacy level of trainees based on their years of study, working experience and grades in English language subjects. Self-efficacy beliefs are formed through the interpretation of performance outcomes which are based on four primary sources of information namely, mastery experience, vicarious experience, social persuasion and physiological reaction. This paper will also discuss on the pedagogical implications of the findings and give recommendations on ways to enhance trainees' self-efficacy level in oral communication ability in English based on these primary sources. Â© 2013 IEEE.